ChatGPT’s Impact Across Sectors: A Systematic Review of Key Themes and Challenges - Hussam Hussein; Madelina Gordon; Cameron Hodgkinson; Robert Foreman; Sumaya Wagad (Big Data and Cognitive Computing)
This paper critically examines the expanding body of literature on ChatGPT, a transformative AI tool with widespread global adoption. By categorising research into six key themes—sustainability, health, education, work, social media, and energy—it explores ChatGPT’s versatility, benefits, and challenges. The findings highlight its potential to enhance productivity, streamline workflows, and improve access to knowledge while also revealing critical limitations, including high energy consumption, informational inaccuracies, and ethical concerns. The paper underscores the need for robust regulatory frameworks, sustainable AI practices, and interdisciplinary collaboration to optimise benefits while mitigating risks. Future research should focus on improving ChatGPT’s reliability, inclusivity, and environmental sustainability to ensure its responsible integration across diverse sectors.